Development of Closed-Circuit Elastic Mounting for Working Bodies in the Interrow Cultivator - Kudzaev, Anatoly Beshtauovich; Korobeinik, Ivan Anatolyevich; Tsgoev, Alan Elbrusovich; Tsgoev, David Valeryanovich; Kalagova, Rita Vladimirovna; Urtaev, Taimuraz Aslanbekovich (Civil Engineering Journal, 2018)
The main drawbacks of cultivators intended for the tillage of stony soils are low reliability of the working bodies, high draught resistance and inability to maintain the required depth of tillage. Hence, the scientists in the Gorsky State Agrarian University conducted a range of studies and trials that allowed them to improve the design. The aim of the present study was to develop a new design of the closed-circuit elastic suspension for the working bodies of a cultivator that is intended for the performance on stony soils and provides high reliability, low draught resistance of the working bodies (in comparison with the existing models), and the required depth of tillage. The tests of the proposed design were performed in the laboratory conditions on a specially designed and constructed stand equipped with tensometric devices. Horizontal and vertical stiffness of the suspension and its frequency was studied. The field trials were performed by a specially constructed machine that was mounted on a tractor. The machine was equipped with tensometric gauges that were reading the sensors with the frequency of 1000 times per second. All the primary data were processed by the respective methods of mathematical statistics. The authors identified the effective model of the closed-circuit elastic suspension for the central working body with the radius of bows R1=125mm, R2=135mm, horizontal stiffness Сhor=25.6 N/mm and natural vibration frequency ν ϵ [10.2…16.2] Hz. A closed-circuit bow type suspension with the stiffness Сhor=18.34 N/mm and natural vibration frequency ν ϵ [8.5…8.7] were most suitable for the side working bodies of a cultivator. It was established that in comparison with the traditional mounting of working bodies, the designed elastic suspension of the working bodies provided the reduction of the draught resistance by 3.7…15%, high reliability and uniform required depth of tillage.